2005
DOI: 10.1021/ja0465404
|View full text |Cite
|
Sign up to set email alerts
|

Amine-Assisted Facetted Etching of CdSe Nanocrystals

Abstract: The treatment of CdSe nanocrystals (NCs) in a 3-amino-1-propanol (APOL)/water (v/v = 10:1) mixture at 80 degrees C in the presence of O(2) causes them to undergo a slow chemical etching process, as evidenced by spectroscopic and structural investigations. Instead of the continuous blue shift expected from a gradual decrease in NC dimensions, a bottleneck behavior was observed with distinct plateaus in the peak position of photoluminescence (PL) and corresponding maxima in PL quantum yield (i.e., 34 +/-7%). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
150
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(159 citation statements)
references
References 35 publications
8
150
1
Order By: Relevance
“…19 The blue shift observed in the PL emission is related to a decrease in the size of the QDs due to surface etching by the APOL/H 2 O solutions and is a demonstration of the quantum confinement effect. This result is in good agreement with the previous study by Li et al 17 However, the blue shift of the PL emission peak in this study is observed to be gradual. This differs from previous studies which have reported a stepwise blue shift.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…19 The blue shift observed in the PL emission is related to a decrease in the size of the QDs due to surface etching by the APOL/H 2 O solutions and is a demonstration of the quantum confinement effect. This result is in good agreement with the previous study by Li et al 17 However, the blue shift of the PL emission peak in this study is observed to be gradual. This differs from previous studies which have reported a stepwise blue shift.…”
Section: Resultssupporting
confidence: 94%
“…The etching time-dependent PL emission spectra with the corresponding absorption spectra are shown in Figure 2(b). The maximum PL emission intensity peak of the as-synthesized QDs observed a wavelength of around 590 nm which is slightly lower than that of the previous samples but much closer to those of the previous study by Li et al 17 The maximum intensity peak also exhibited a clear blue shift with increasing time however the FWHM showed only a slight increase (after 1 h).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The presence of halogen compounds in the synthesis of semiconductor nanocrystals (NCs) produced by hot injection [1] drastically influences their capping ligand sphere and/or their chemical reactivity [2][3][4][5], allowing for the growth of hybrid systems [6], including composites of NCs decorating carbon sp 2 surfaces [7]. Several works have reported on chemical and photochemical processes taking place during the growth of semiconductor NCs in the presence of halide or acetate anions [8].…”
Section: Introductionmentioning
confidence: 99%